Comparative Analysis of Selected Animal and Vegetable Oils Suitability in Machining of Plain Carbon Steels - Alabi Ismaila Olanrewaju; Okediji Adebunmi Peter; Ogedengbe Temitayo Samson; Joseph Ojotu Ijiwo; Olukokun Tolulope Opeyemi (International Journal of Engineering and Management Research, 2019)
Due to the alarming rate in public awareness on environmental issues, there has been growing demand for biodegradable materials which has opened an avenue for using vegetable and animal oils as alternatives to petroleum-based polymeric materials in the market, most especially in machining operations. Thus, research on biodegradable functional fluids has emerged as one of the top priorities in lubrication, due to their applicability in many diverse areas. In this quest, there is need to conduct machining trials to determine the suitability of these oils in metal cutting (turning) operations of plain carbon steels. This study investigate the effect of the selected cutting fluids on certain parameters like machine removal rate (MRR), machining time, tool wear and spindle power consumption, etc. under different machining combination in turning operations of plain carbon steels obtained from universal steel Ikeja, Nigeria, using 150 x 10 HSS cutting tool. The selected oils purchased from Ogunpa market in Ibadan, Nigeria, were sieved to remove any foreign particles or dirt. The solution; water, based-oil, and emulsifier (to allow thorough mixing of water and oil without separation), were mix at an elevated temperature of 550C in a proportion 4:1:3. Experimental results clearly showed that Conventional cutting fluid might be replaced with Non-conventional cutting fluids (vegetable and animal based) as they give better performance. With slight modifications and deliberate but careful alterations in some of the components of such oils, even better performing cutting fluids could be obtained.